Home alarm system - Zifungo, Delbert E. (Midlands State University, 2018)
The crime rate in the nation of Zimbabwe has been steadily increasing in the past 3 years with about 10-15% annually and particularly in theft related crimes. It is due to the advent of this growth in crime that has led to the development of this system as a basis of a prototype to protect people’s homes in particular. As the study in crime done by the ZRP and U.S Embassy OSAC the crimes are mainly based on breaking and entering, therefore this Arduino based alarm system is developed to detect intrusions in the vicinity is deemed a necessary improvement. It works with several pre-existing technologies to make a compound system through several components such as PIR motion sensors, Magnetic Contact Reed Switches and Ultrasonic sensors. This document highlights the several stages involved in the project from its initiation to the assembly of the system into a working prototype. The reader can therefore understand the steps that help them in coming up with a similar system and the amount of work and research involved. Through the explanations offered the reader can get an appreciation of concepts in electronics and the problem solving approach herein.